The emerging importance of tranexamic acid in dermatology. (30th October 2019) - Forbat, E.; Al‐Niaimi, F.; Ali, F.R.
Summary: Tranexamic acid (TA) is an antifibrinolytic agent, increasingly recognized as being of utility for a wide variety of skin diseases. We review the evidence supporting the use of TA for a range of dermatological indications, including (among others) melasma, postinflammatory hyperpigmentation, urticaria, angio‐oedema and haemostasis, in addition to practical considerations of its use by dermatologists. Abstract : Click here for the corresponding questions to this CME article.